Aspirations and the role of social protection: Evidence from a natural disaster in rural Pakistan - Kosec, Katrina; Mo, Cecilia Hyunjung (International Food Policy Research Institute, 2015)
Citizens’ aspirations for the future are politically important; they are linked to welfare and whether citizens engage in forward-looking political and economic behavior. How do natural disasters affect aspirations, and can governments’ social protection policies successfully mitigate any damaging effects? If natural disasters threaten aspirations, there is strong policy interest in understanding these threats and what government can do to protect aspirations. This article uses Pakistan’s 2010 floods to identify the effects of a natural disaster on citizens’ aspirations. Aspirations were significantly reduced—especially among the poorest and most vulnerable. However, by exploiting exogenous variation in access to targeted government social protection, the authors show that social protection following natural disasters can significantly reduce their negative aspirational effects. This offers a new understanding of government social protection. It not only raises social welfare in the short term by restoring livelihoods and replacing damaged assets; it also has an enduring effect by raising citizens’ aspirations for the future. The authors show not only that the aspirations of citizens matter for citizens’ behaviors, but also that government policies can effectively protect and increase those aspirations. This implies that the value and efficacy of government disaster relief programs are underestimated when aspirations are not taken into account.